Design of Integrated Data Management System for Sustainability Reporting and Program for Manufacturing Industries in Indonesia - Priskila Christine Rahayu; Daisy Amanda; Jessica Hanafi (Indonesian Life Cycle Assessment Network (ILCAN), 2018)
The manufacturing industry and its relationship with sustainable development simply cannot be separated. Especially, when the government started to show their attention by giving various obligations for the manufacturing industry to implement sustainable development principles, such as the obligation of the company to conduct a social and environmental responsibility by making sustainability report, the environmental impact assessment (AMDAL) report, to participate in various sustainability programs such as Corporate Performance Rating Program (PROPER) and Green Industry Award. There are so many indicators and data that need to be collected in order to fulfill these obligations. It certainly may charge the company in terms of time, yet the number of indicators and the data required were similar between one report to another. There is still no particular design to be able to resolve the issue. Therefore, the aim of this study is to design an integrated data management system for sustainability reporting needs and sustainability programs which has the end result of an application prototype of a system that can help companies, especially in the manufacturing industry to create reporting even more efficient. Data management is done by combining all four types of reporting and program which are Global Report Initiative sustainability report, the AMDAL report, Green Industry program, and PROPER. The prototype is made based on the results of data management using Microsoft Access to store data and to produce four types of summary reports. In the end of the study, it can be concluded that, overall, the system can be implemented and by the withdrawal of three respondents review, the system can improve the efficiency of the company in preparing sustainability reporting. In the evaluation phase, it is found a related method that can be used as the basis to do before making reporting in order to make them more easily 40.98%, that is Life Cycle Assessment.